Sistema de control interno aplicado al proceso constructivo de viviendas de hormigón armado en proyectos urbanísticos - Garcés Alava, Magali Solange (2021)
In this research work that entitled "Internal Control System applied to the Construction Process of Reinforced Concrete Homes in Urban Projects", literature has been reviewed about the threats that the construction sector approach in terms of project performance. , where the shortage of internal control constitutes one of them, this causes a failed construction process that brings with it the non-compliance of times and estimated costs in the planning of the work, as well as the lack of quality in the delivered product. The information based on project management shows the different methodologies used in the construction industry to control the construction process, which are justified with a normative that regulates construction projects in the country, considering these parameters are proposes to use the SIPOC project management tool and the development of a procedures manual that synthesizes and orders the tasks to do in each area that is part of the construction process of Reinforced Concrete Homes, in order to achieve with schedules and budgets assigned in the planning stage and avoid post-sales actions at the end of the work........